DAMPAK PANDEMI COVID-19 TERHADAP PENDAPATAN PETANI HORTIKULTURA DI DESA SEBERAYA, KECAMATAN TIGAPANAH, KABUPATEN KARO, PROVINSI SUMATERA UTARA - Dorlan Yolanda Br Ritonga; Deded Chandra (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
ABSTRACT This study aims to look at the income of horticultural farmers before and after the pandemic and farming strategies carried out by farmers before and after the Covid-19 pandemic in Seberaya Village, Tigapanah District, Karo Regency, North Sumatera Province. The research method used is descriptive quantitative with research subjects namely horticultural farmers. Data was collected by means of interviews and giving questionnaries to 41 respondents. The results of the study found that farmers’ income increased and decreased during the pandemic, this was caused several agricultural commodities experienced price instability, commodities that experienced price increases were potatoes Rp.2.000/kg, carrots Rp.500/kg, tomatoes Rp.2.000/kg, while commodities that experienced a decline in prices were cabbage Rp.1.600/kg and chili Rp.17.000/kg. Then there was no change in the strategy of cropping patterns carried out by farmers before and during the pandemic. Keywords: Covid-19 Pandemi, Income, Cropping Patterns